Contribuições do estágio supervisionado para a formação inicial de professores alfabetizadores - Barros, Zian Karla Vasconcelos (2025)
This thesis is part of the research line Educational Process and Teacher Training, of the Stricto Sensu Postgraduate Program in Education, of the Catholic University of Brasília. Its object of study is the discipline of Supervised Internship II: Initial Years of Elementary School, as a theoretical-practical contribution to the initial training of literacy teachers. The general objective is to analyze the initial training of literacy teachers as a challenge for the discipline of Supervised Internship II: Initial Years of Elementary School, considering the documentary research, the perception of teachers, graduates and students of the Pedagogy Course of the CEHS of Tocantinópolis. The specific objectives are: to relate propositions, syllabuses and interactions contained in disciplines associated with the teaching of the Portuguese Language and the Supervised Internship II: Initial Years of Elementary Education, constant in the PPC (2023) of the Pedagogy Course at UFNT/CEHS in Tocantinópolis, which corroborate the initial training process of literacy teachers; to identify knowledge, expectations and actions (theoretical and practical), related to the training of the literacy teacher, expected within the scope of initial training, according to the teachers responsible for the disciplines related to the teaching of the Portuguese Language and the Supervised Internship, in the Pedagogy Course at UFNT/CEHS in Tocantinópolis and to evaluate the place that has been given to the theme of literacy, in the set of theoretical-practical actions of the Supervised Internship II, of the Pedagogy course, according to the perception of students who graduated from the aforementioned discipline and graduates of the course who are working in classes from the 1st to the 5th year in the municipal education network. It is anchored in theoretical and legal postulates that corroborated to support the analyses and discussions that emerged in search of an answer to the following problem-question: How has the discipline, Supervised Internship II: Initial Years of Elementary School, been affected by the theme of literacy and what has been its direction regarding the initial training process of literacy teachers? The investigative scenario was revealed from the results arising from the State of Knowledge, which found gaps in studies involving Supervised Internship in Pedagogy courses, with a focus on the initial training of literacy teachers, presented as one of the indicators of the originality of this research. The theoretical framework contemplated questions about the relevance of Supervised Internship for the initial training of pedagogues, presented reflections on literacy and teacher training in Brazil. The methodological approach is qualitative. It is an applied research in nature, and its objectives are explanatory. It is a field research, which was carried out through documentary research, semi-structured interviews, and questionnaires (Google Forms). The Discursive Textual Analysis methodology was used to analyze the data. The results indicated that the Supervised Internship II discipline has been dealing with the theme of literacy, which, despite not being predominantly directed at the initial training of literacy teachers, can contribute significantly to this training process. They also pointed out, as a practical contribution, some issues that need to be realigned in the pedagogy course so that the discipline in question can contribute to the initial training of literacy teachers.